Halopseudomonas species: Cultivation and molecular genetic tools - Luzie Kruse; Anita Loeschcke; Jan deWitt; Nick Wierckx; Karl‐Erich Jaeger; Stephan Thies (Microbial Biotechnology, 2024)
Abstract The Halopseudomonas species, formerly classified as Pseudomonas pertucinogena lineage, form a unique phylogenetic branch within the Pseudomonads. Most strains have recently been isolated from challenging habitats including oil‐ or metal‐polluted sites, deep sea, and intertidal zones, suggesting innate resilience to physical and chemical stresses. Despite their comparably small genomes, these bacteria synthesise several biomolecules with biotechnological potential and a role in the degradation of anthropogenic pollutants has been suggested for some Halopseudomonads. Until now, these bacteria are not readily amenable to existing cultivation and cloning methods. We addressed these limitations by selecting four Halopseudomonas strains of particular interest, namely H. aestusnigri, H. bauzanensis, H. litoralis, and H. oceani to establish microbiological and molecular genetic methods. We found that C4‐C10 dicarboxylic acids serve as viable carbon sources in both complex and mineral salt cultivation media. We also developed plasmid DNA transfer protocols and assessed vectors with different origins of replication and promoters inducible with isopropyl‐β‐d‐thiogalactopyranoside, l‐arabinose, and salicylate. Furthermore, we have demonstrated the simultaneous genomic integration of expression cassettes into one and two attTn7 integration sites. Our results provide a valuable toolbox for constructing robust chassis strains and highlight the biotechnological potential of Halopseudomonas strains.